THE INFLUENCE OF OPTIMIZED TECHNICAL TRAINING ON SPECIFIC MOVEMENT QUALITIES IN 13-14-YEAR-OLD FOOTBALL PLAYERS - ChoriyevDilshod Ismat o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article is aimed at methodically helping to improve the technical training of young football players and how it affects the qualities of special movements in ball control, as well as developing a set of special exercises for young football players. Analysis of the dynamics of size and quality indicators of technical-tactical movements and comprehensive development of physical abilities, increasing physical qualities such as quickness, endurance, agility, test results of technical movements, and the number and efficiency of technical-tactical movements performed by football players are highlighted on the basis of tables. focused on giving.